2018
DOI: 10.1038/aps.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Predicting functional outcome of ischemic stroke patients in Romania based on plasma CRP, sTNFR-1, D-Dimers, NGAL and NSE measured using a biochip array

Abstract: In cerebral ischemia, evaluation of multiple biomarkers involved in various pathological pathways is a useful tool in assessing the outcome of the patients even from the early stages of the disease. In this study we investigated the utility of a panel of 5 peripheral biomarkers of inflammatory status, neuronal destruction and secondary fibrinolysis in the acute phase of ischemia, and evaluated the impact of these biomarkers on functional outcome after ischemic stroke. The 5 biomarkers (plasma CRP, D-Dimers, sT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
2
34
1
Order By: Relevance
“…One of the recent challenging multiple biomarker screening (255 plasma proteins) was performed from the ARIS-TOTLE trial in order to identify novel prognostic markers for major bleeding in patients with atrial fibrillation on oral anticoagulation (20). In our population we measured a panel of five peripheral biomarkers for neuronal damage, inflammation, and fibrinolysis and we found that D-Dimers and sTNFR-1 have increased discrimination ability to classify poor functional outcome at 3 months after ischemic stroke (21).…”
Section: Multimarker Approach In Precision Medicinementioning
confidence: 98%
“…One of the recent challenging multiple biomarker screening (255 plasma proteins) was performed from the ARIS-TOTLE trial in order to identify novel prognostic markers for major bleeding in patients with atrial fibrillation on oral anticoagulation (20). In our population we measured a panel of five peripheral biomarkers for neuronal damage, inflammation, and fibrinolysis and we found that D-Dimers and sTNFR-1 have increased discrimination ability to classify poor functional outcome at 3 months after ischemic stroke (21).…”
Section: Multimarker Approach In Precision Medicinementioning
confidence: 98%
“…Indeed, TNF-α’s appearance in the brain following the damage induced by ischemia is quick and has a first peak in the early hours [1–3 h] and a successive one after more than 24–36 h [ 34 , 35 ]. In the literature, some reports indicate that TNF-α represents an accurate indicator that can be useful to define the beginning of the inflammatory reaction and a helpful one for the evaluation of the patient’s outcome [ 36 ]. A rising quantity of TNF-α can be seen in patients affected by a stroke just 6–12 h following the appearance of the symptomatology [ 37 ].…”
Section: Roles Of Cytokines In Cerebral Ischemiamentioning
confidence: 99%
“…88 The authors claim that TNF-α is a sensitive parameter determining the onset of an inflammatory response and a useful indicator for the assessment of prognosis. 65,89 An increase in the concentration of TNF-α is observed in stroke patients as soon as 6-12 hrs after the onset of symptoms. 47 An increase in TNF-α concentration within 24 and 48 hrs after a stroke has also been shown, and the observed slow decrease occurring within 72 and 144 hrs after a stroke correlates with a clinical improvement in patients in the acute phase of ischemic stroke.…”
Section: Tnf-α In Strokesmentioning
confidence: 99%